1995
DOI: 10.1103/physrevlett.74.1920
|View full text |Cite
|
Sign up to set email alerts
|

Superinstantons and the Reliability of Perturbation Theory in Non-Abelian Models

Abstract: In dimension D ≤ 2 the low temperature behavior of systems enjoying a continuous symmetry is dominated by super-instantons: classical configurations of arbitrarily low energy. Perturbation theory in the background of a super-instanton produces thermodynamic answers for the invariant Green's functions that differ from the standard ones, but only in non-Abelian models and only starting at O(1/β 2 ). This effect modifies the β-function of the O(N ) models and persists in the large N limit of the O(N ) models.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
67
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 46 publications
(70 citation statements)
references
References 5 publications
(5 reference statements)
3
67
0
Order By: Relevance
“…For earlier counterevidence to both the physical KT picture as well as the quantitative essential scaling predictions see [40,41,42] and [13,39]. Further criticisms of the conventional view are found in [43].…”
Section: The Step Modelmentioning
confidence: 99%
“…For earlier counterevidence to both the physical KT picture as well as the quantitative essential scaling predictions see [40,41,42] and [13,39]. Further criticisms of the conventional view are found in [43].…”
Section: The Step Modelmentioning
confidence: 99%
“…In his recent Comment [1] on our Physical Review Letter [2], David accepts our computations but challenges our conclusion that in non-Abelian models perturbation theory (PT) is untrustworthy even at short distances. Moreover, he claims that if one 'renormalizes' PT appropriately, one recovers the standard answers, such as the known Callan-Symanzik β-function.…”
mentioning
confidence: 94%
“…We have nothing to contribute to (ii), but some new computations confirming (i) beyond what was stated in [2]. All our computations, just as those of [1,2] refer to a special obervable, namely the nearest neighbor spin-spin scalar product located in the center of the lattice, i.e. O = s(0, 0) · s(0, 1).…”
Section: The Arguments Of [2] Rely On Two Conjecturesmentioning
confidence: 97%
“…Several years ago A. Patrascioiu and the second-named author [1] investigated the dependence of perturbation theory (PT) on boundary conditions (b.c.). Surprisingly they found that in two-dimensional nonlinear sigmamodels with non-abelian symmetry the coefficients of the perturbative expansion depend on the boundary conditions (b.c.)…”
Section: Introductionmentioning
confidence: 99%